EVALUATION OF NON H. PYLORI SPIRAL ORGANISMS IN HUMAN GASTRIC BIOPSIES BY USING PCR AND MICROSCOPIC METHODS IN IRAN (FIRST REPORT) - Bahadori, A.; Esmaeillu, M.; Sadighbayan, KH.; Bahadori, F.; Jabbari, M.V.; Attarhosseani, M.; mobaiyen, H.; pourfeizi, Z. Hossein (European Scientific Journal, ESJ, 2013)
Introduction and Objectives: The Discovery of Helicobacter pylori in 1982 increased interest in the range of other spiral bacteria that had been seen in Stomach (Marshall & Warren 1984).The power of technologies such as the polymerase chain reaction (PCR) with genus specific primers revealed that many of these bacteria belong to the genus Helicobacter. These nonpylori helicobacters are increasingly being found in human clinical specimens. Non-pylori Helicobacters are Gram-negative, motile, long, tightly coiled, Spiral bacteria ,with three to eight coils, that cause of some gastric problems like gastritis, peptic ulceration and Mcosa-Associated Lymphoid Tissue (MALT) lynphoma in animals and humans. Materials and Methods: Samples taken during endoscopy were analyzed by rapid urease test, PCR and light microscope(Giemsa and Gram staining). In this study 270 samples were collected from Patients with gastric disorders. Presence of Helicobacters confirmed by a positive urease test and Helicobacter genus specific PCR method utilized. DNA was prepared from biopsies using the Qiamp tissue kit (QIAGEN Inc., Valencia, Calif.) and frozen at âˆ’20Â°C (like gastric samples/biopsies). DNA samples that PCR positive were amplified with 16SrRNA gene primers against Helicobacter species. Results: In gastric biopsy specimen's non-pylori helicobacter spp., have been observed. At the end of the study we found that 71% of urease tests, 0.37% of light microscopic studies (we observed some spiral gram negative bacteria with 2-7 coils) and 0.74% of PCR tests were positive. In analysis with PCR route 2 person (both of them were Male) were infected with H.heilmanniilike organisms( one of them kept a dog for 5 years as a pet).16S rRNA gene amplification was performed on 270 DNA samples and results were positive for H.heilmannii in two cases (275-bp), but negative for H.bizzozeronnii,H.felis and H. Salmonis.